Low Serum Cholinesterase Identifies Patients With Worse Outcome and Increased Mortality After TIPS. Issue 3 (28th September 2021) - Stockhoff, Lena; Muellner‐Bucsics, Theresa; Markova, Antoaneta A.; Schultalbers, Marie; Keimburg, Simone A.; Tergast, Tammo L.; Hinrichs, Jan B.; Simon, Nicolas; Gerbel, Svetlana; Manns, Michael P.; Mandorfer, Mattias; Cornberg, Markus; et al.
Abstract : Transjugular intrahepatic portosystemic shunt (TIPS) is an effective treatment for portal hypertension‐related complications. However, careful selection of patients is crucial. The aim of this study was to evaluate the prognostic value of serum cholinesterase (CHE) for outcomes and mortality after TIPS insertion. In this multicenter study, 389 consecutive patients with cirrhosis receiving a TIPS at Hannover Medical School, University Hospital Essen, or Medical University of Vienna were included. The Hannover cohort (n = 200) was used to initially explore the role of CHE, whereas patients from Essen and Vienna served as a validation cohort (n = 189). Median age of the patients was 58 years and median Model for End‐Stage Liver Disease (MELD) score was 12. Multivariable analysis identified MELD score (hazard ratio [HR]: 1.16; P  < 0.001) and CHE (HR: 0.61; P = 0.008) as independent predictors for 1‐year survival. Using the Youden Index, a CHE of 2.5 kU/L was identified as optimal threshold to predict post‐TIPS survival in the Hannover cohort ( P  < 0.001), which was confirmed in the validation cohort ( P = 0.010). CHE < 2.5 kU/L was significantly associated with development of acute‐on‐chronic liver failure ( P  < 0.001) and hepatic encephalopathy ( P = 0.006). Of note, CHE was also significantly linked to mortality in the subgroup of patients with refractory ascites ( P = 0.001) as well as in patients with high MELD scores ( P = 0.012) and with high‐risk FIPS scores ( P = 0.004). After propensity score matching, mortality was similar in patients with ascites and CHE < 2.5 kU/L if treated by TIPS or by paracentesis. Contrarily, in patients with CHE ≥ 2.5 kU/L survival was significantly improved by TIPS as compared to treatment with paracentesis ( P  < 0.001). Conclusion: CHE is significantly associated with mortality and complications after TIPS insertion. Therefore, we suggest that CHE should be evaluated as an additional parameter for selecting patients for TIPS implantation. Abstract : Transjugular intrahepatic portosystemic shunt (TIPS) is an highly effective therapy for complications of portal hypertension. Adequate selection of patients eligible for TIPS is crucial, but the criteria are not yet well‐established. We found that serum Cholinesterase activity is an independent predictor for complications as well as mortality after TIPS insertion.image